Technology Utilization for Soil Productivity Enhancement of Large-Scale Rice Farmers in Sapphaya District, Chai Nat Province - Kasak, Nuttha; Srisuwan, Supattra; Choocharoen, Chalathon (Journal of Roi Et Rajabhat University, 2026)
The objectives of this research were: 1) to study the personal, economic, and information exposure factors of large-scale rice farmers in Sapphaya District; 2) to investigate technology utilization for soil productivity enhancement of large-scale rice farmers; and 3) to compare personal, economic, and information exposure factors and technology utilization. The samples consisted of 122 large-scale rice farmers in Sapphaya District, Chainat Province. Data were collected through interviews and analyzed by using descriptive statistics, including frequency, percentage, mean, and standard deviation. Hypotheses were tested by using t-test, and F-test and pairwise differences were examined using the LSD method. The research results revealed that: 1) Farmers had an average age of 57.57 years, an average of 25.99 years of rice farming experience, and an average number of laborers was 5.70 persons. Farmers received information from government extension officers through personal media 63.10%, and mass media from television 51.60%. 2) The overall level of technology utilization for soil productivity enhancement in rice paddies was moderate level, with a mean of 2.18, including technologies for rice straw and stubble management, land leveling, and soil nutrient management. 3) Farmers with different levels of rice farming experience, number of laborers, exposure to personal media and mass media information had significantly different levels of technology utilization for soil productivity enhancement in rice paddies at the 0.05 significance level. Additionally, farmers of different genders showed significant differences in technology utilization for soil productivity enhancement in rice paddies at the 0.01 significance level.